Electrical instability of induction motor driven by CSI with output capacitors - Song, J.-H.; Kim, K.-B.; Youn, M.-J. (Proceedings of Power Conversion Conference - Yokohama 1993, 1993)
A load commutated current source inverter (LCCSI)-fed induction motor system, where large output capacitors are provided to perform the load commutation, is faced with an electrical instability problem. An electrical instability analysis of the LCCSI-fed induction motor drive system is done by evaluating the eigenvalues of the resulting system matrix. It is also shown that a proposed compensation method can permit the LCCSI-fed induction motor drive system to avoid the electrical instability problem under the nominal operating frequency region. ？ 1993 IEEE.